(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
The use of Traditional medicinal products continues to grow rapidly across all over the world while the safety of these products has been raised. As the last century saw a predominance of communicable disorders this century can be considered as a century of Non communicable Diseases. The main issue here is people consuming traditional medicine along with contemporary with a preoccupied thought that these medicines are free from adverse effects. But all traditional systems are not like that. Ayurveda which is a complete and ancient system with the present aim of accomplishment of physical, mental, social and spiritual well being at a global front. Even though substitution, adulteration, improper focus on quality is pulling down the popularity of Ayurveda, hence purity and safety of Ayurvedic medicines along with strict Standardization is need of an hour.